Choral vocalization and mono-vocalism: A contextual analysis - Vladimirovich Krasov, Vladimir (Opción, 2019)
The article aims to investigate choral vocalization and mono-vocalism as a special phenomenon in modern Russian music on the example of the composition of Sergei Terentyev via combining historical-stylistic, system-genre, literary-stylistic methods of analysis. As a result, choral vocalization is a frequently used choral technique widely used in modern sonorous choral music. In conclusion, the necessity of contextual analysis of various pieces of music has been proved. Depending on the synthesis of the different arts, the approach to the analysis of each will be individual